2017
DOI: 10.5171/2017.246481
|View full text |Cite
|
Sign up to set email alerts
|

The Ethics of Students’ Behavior: Between Intentions, Judgment and Action

Abstract: Consumption behavior -not long ago a neglected and marginalized domain -has shifted its focus towards exploring questionable ethical behaviors. While in the past consumers were questioned especially with regard to their opinions as to business ethics, today they are questioned as to the ethics of their consumption behavior. This study focuses upon the possible explanations of ethically questionable consumer behavior, namely the ethics of students' behavior from a comparative perspective: the students from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Sing and Verma (2017) presented the same result, that income is a potential factor that influences actual behaviour towards ethical products. Also, a study by Coman et al (2016) confirmed that income or economic situation, in general, has a significant impact on the actual preference for ethical products in purchasing decisions. Ethical food consumption, as a specific area of ethical shopping, is also framed in the accounts of people living in affluent societies.…”
Section: Discussionmentioning
confidence: 85%
“…Sing and Verma (2017) presented the same result, that income is a potential factor that influences actual behaviour towards ethical products. Also, a study by Coman et al (2016) confirmed that income or economic situation, in general, has a significant impact on the actual preference for ethical products in purchasing decisions. Ethical food consumption, as a specific area of ethical shopping, is also framed in the accounts of people living in affluent societies.…”
Section: Discussionmentioning
confidence: 85%